Separation anxiety : a novel - Zigman, Laura (Ecco,Âan imprint of HarperCollinsPublishers, 2020)
Judy never intended to start wearing the dog. But when she stumbled across her son Teddy<U+2019>s old baby sling during a halfhearted basement cleaning, something in her snapped. So: the dog went into the sling, Judy felt connected to another living being, and she<U+2019>s repeated the process every day since. Life hasn<U+2019>t gone according to Judy<U+2019>s plan. Her career as a children<U+2019>s book author offered a glimpse of success before taking an embarrassing nose dive. Teddy, now a teenager, treats her with some combination of mortification and indifference. Her best friend is dying. And her husband, Gary, has become a pot-addled professional “snackologist” who she can<U+2019>t afford to divorce. On top of it all, she has a painfully ironic job writing articles for a self-help website<U+2014>a poor fit for someone seemingly incapable of helping herself. Wickedly funny and surprisingly tender, Separation Anxiety offers a frank portrait of middle-aged limbo, examining the ebb and flow of life<U+2019>s most important relationships. Tapping into the insecurities and anxieties that most of us keep under wraps, and with a voice that is at once gleefully irreverent and genuinely touching, Laura Zigman has crafted a new classic for anyone taking fumbling steps toward happiness.